Disturbance observer–based control for missile non-strapdown seeker disturbance rejection. (15th April 2016) - Song, Tao; Lin, Defu; Wang, Jiang
Non-strapdown seeker disturbances which involve counter-electromotive force, spring restoring torque, and friction torque can corrupt the seeker tracking accuracy and degrade the missile guidance performance. In this article, the effects of guidance parameters and disturbances on the guidance stability and the miss distance are analyzed. It is shown that these disturbances have a pronounced deterioration in the guidance performance for the anti-air missile under high altitude and head-on interception. A new approach for disturbance rejection using disturbance observer–based control is presented. Disturbances in seeker stabilizing loop are estimated by the observer which has synthetic inputs based on the available seeker measurement signals. The estimates are fed back into the seeker inner loop to compensate the disturbances, and an additional loop is applied to improve the effect of disturbance compensation. The performance of the approach under non-nominal condition is analyzed. Simulation studies are performed to examine the effect of this control scheme. The result shows that this approach can effectively reduce the influences of corrupting disturbances and significantly improve the miss distance performance.